U.S. Young Adults' Professional Help-Seeking in Response to Technology-Facilitated Abuse. Issue 11 (June 2023) - Mumford, Elizabeth A.; Rothman, Emily F.; Maitra, Poulami; Sheridan-Johnson, Jackie
Widespread access to an increasing number of technology-enhanced communications channels multiplies the potential for abusive interactions (i.e., technology-facilitated abuse [TFA]). Practitioners will be better prepared to respond to the problem of TFA if more is known about how commonly victims seek help, and from whom. Through a cross-sectional, U.S. nationally representative survey of n = 1, 215 young adults aged 18 to 35, respondents completed the TFA scale of the Cyber-Abuse Research Initiative. We calculated the percentage of TFA survivors who sought help for their most damaging experience of TFA, and used logistic regression to model help-seeking for health services, victim services, technological assistance, and/or criminal justice/legal assistance. For each help source, we examined risk markers including sociodemographic characteristics, online activity, the number of different forms of TFA experience, and the perpetrator's relationship to the victim. Use of a broader range of social media sites/platforms, and several indicators of more severe TFA experiences, predicted help-seeking from health services, victim services, and justice/legal assistance. Young adults who identified the TFA perpetrator as a current or ex-intimate partner were less likely than other survivors to seek two forms of help: technological assistance and/or criminal justice/legal assistance. Survivors who self-identified as Black were more likely than White survivors to seek victim services. Professionals who support survivors of interpersonal aggression may use these results to enhance their screening protocols and form cross-disciplinary partnerships to address the harms associated with TFA.